ANALYSIS OF THE INFLUENCE OF FINANCIAL PERFORMANCE ON COMPANY VALUE (CASE STUDY AT PT SOLUSI BANGUN INDONESIA, TBK) - Sutisna, Eka; Saksono, Lalang; Febriana, Dwi Cahyani (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to determine the effect of Financial Performance which referred to Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and Return on Equity (ROE) on Firm Value which referred to Price to Book Value (PBV). The type of this research is quantitative. The population of this research is manufacturing companies sub sector material, however this research is focused on PT Solusi Bangun Indonesia Tbk. The sample for this research is financial report of 2019-2022. The data analysis technique used in this research is Classical Assumption Test, while hypothesis test is performed by using Multiple Regression Analysis, which includes a smilutaneous Significance Test (f test) and Partial Significance Test (t test). The results of this research is (1) CR, DER, TATO, ROE simultaneously had a positive and significance effect on Firm Value. (2) CR had no effect on Firm Value. (3) DER had a positive and significance effect on Firm Value. (4) TATO had no effect on Firm Value. (5) ROE had a positive and significance effect on Firm Value.